Plan de negocios para la comercialización de cepillos rotativos desestresantes, desparasitantes y de limpieza, para vacas en la provincia de Pichincha cantón Mejía - Tinajero Cisneros, Bertha Lucia (2018)
The business plan for the marketing of rotating brushes, deworming, de-stressing and cleaning for cows, seeks to satisfy the needs of the livestock market in finding comfort and animal welfare, as well as increasing its milk production, in the province of Pichincha, canton Mejia. Project that will be carried out through the production and commercialization of rotating brushes under the brand “Rascamu”, whose main function is to provide well-being, through a rotating movement, on the skin of the animal, producing a sensation of relaxation and anti-stress. In turn, the brush fulfills another important function, as it is antiparasitic, that is, it eliminates external parasites or ectoparasites; lies, fleas and ticks. Finally allowing the farmer to reduce labor and unnecessary expenses. Rascamu is a company that will distribute its brushes directly to the rancher in their farms. This product is aimed at farmers of 20-40 years, of a medium or medium high socio-economic level, of the canton Mejia seeking the care and welfare of the animal, using a new technology. An analysis of the external environment was developed, using the PEST tool (Political, Economic, Social and Technological) and a PORTER analysis, to know both the opportunities and threats of the industry. Additionally, a market study was developed, product of which the target market could be identified, and a marketing plan was made to prepare the product, price, and place and promotion strategies. On the other hand, a business philosophy was generated, in which the mission, vision, values and objectives of the company are detailed, to inform the company and reflect a horizon. An operative plan was elaborated in which the hierarchic system of the company was designed, as well as the establishment of roles of each employee, functions and obligations. Finally, a financial analysis was carried out, which through indicators it was possible to determine that the project is viable, with a low investment and an attractive rate of return for the investor.